New Tendencies in the Turkish Language - Teodosijević, Mirjana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
Following the establishment of the Republic of Turkey on the 29th of October 1923, Mustapha Kemal Ataturk began the implementation of fundamental reforms for the creation of a new identity for the Turkish nation. One of the most important reforms was the adoption of Latin script in place of Arabic, as well as the cleansing of the Turkish language of Arabic and Persian linguistic influence and borrowed words. It is from then onwards that the Turkish language began to change continually and was modelled under the control of the Turkish Linguistic Society in whose undertakings numerous linguists, writers and cultural workers took part. Many books were published: grammar books that established norms for the Turkish language, single-language dictionaries, dictionaries of neologism to replace archaic and Ottoman words, dual-language dictionaries, orthographic rule books, professional and scientific journals, as well as organizing many Turkish Language congresses in which all aspects and issues related to language usage were discussed and studied. Since it is a known fact that languages are constantly undergoing transformation in space and time, all these changes, especially during the last twenty years, had been under the watchful eyes of numerous linguists who were responsible for scrutinizing all relevant aspects of the language on the grammatical, lexical and socio-cultural levels. However, many of these changes had not been promptly and adequately processed in the relevant Turkish language grammar books, a fact that today poses a special problem for persons studying the Turkish language. Thus, in this paper we have focused our attention solely on atypical usage of the language on grammatical and lexical levels, without carrying out any deeper analysis of those instances because such an undertaking would require of us to enter the domain of linguistic field-work research.
Keywords: Anglo-Saxon loan words; Turkish language deterioration; participles; status constructus; exclusion of suffixes; new tendencies; Turkish language